An engineered pancreatic cancer model with intra-tumoral heterogeneity of driver mutations. Issue 20 (10th September 2020) - Moon, Hye-ran; Ozcelikkale, Altug; Yang, Yi; Elzey, Bennett D.; Konieczny, Stephen F.; Han, Bumsoo
Abstract : We present a microfluidic tumor model with intra-tumoral heterogeneity of key driver mutations of pancreatic cancers including Kras, p16 and p53. We demonstrate its potential use of drug screening, and identify a new drug resistance mechanism. Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a complex disease with significant intra-tumoral heterogeneity (ITH). Currently, no reliable PDAC tumor model is available that can present ITH profiles in a controlled manner. We develop an in vitro microfluidic tumor model mimicking the heterogeneous accumulation of key driver mutations of human PDAC using cancer cells derived from genetically engineered mouse models. These murine pancreatic cancer cell lines have KPC ( Kras and Trp53 mutations) and KIC genotypes ( Kras mutation and Cdkn2a deletion). Also, the KIC genotypes have two distinct phenotypes – mesenchymal or epithelial. The tumor model mimics the ITH of human PDAC to study the effects of ITH on the gemcitabine response. The results show gemcitabine resistance induced by ITH. Remarkably, it shows that cancer cell–cell interactions induce the gemcitabine resistance potentially through epithelial–mesenchymal-transition. The tumor model can provide a useful testbed to study interaction mechanisms between heterogeneous cancer cell subpopulations.